The Influence of Hard and Soft Magnetic Nanoparticle Additives in Magnetorheological Fluids on the Performance of Magnetorheological Dampers for Motorcycle - Rahmad Rizki Nur Arifin; Bhre Wangsa Lenggana; Ubaidillah Ubaidillah; Irfan Bahiuddin; Kacuk Cikal Nugroho; Fitrian Imaduddin; Saiful Amri Mazlan; Arjon Turnip (Universitas Muhammadiyah Magelang, 2026)
Magnetorheological Fluids (MRFs) are widely utilised in semi-active suspension systems due to the ability to dynamically alter their viscosity. The frequently issue in the application of MRFs are sedimentation and aggregation stability. To address this issue, the MRFs have been modified by incorporating hard and soft magnetic nanoparticles. The MRFs investigated were MRF-carbonyl iron powder (CIP), MRF-CIP+cobalt ferrite (CoFe2O4), and MRF-CIP+manganese ferrite (MnFe2O4). The objective of this work is to evaluate the performance of these MRFs to implement the results to motorcycle dampers. To ascertain the MRFs’ magnetic properties and viscosity (Î·), vibrating sample magnetometer (VSM) and rheometer testing were conducted, respectively. The performance of magnetorheological valve (MRV) was analysed using finite element method magnetics (FEMM) simulations with variations in fluid gaps and types of MRFs. The results indicated that the MRV design with a fluid gap of 0.9 mm, utilizing MRF-CIP+CoFe2O4, exhibited an appropriate combination to fulfil the damping force (Fd) requirements of the motorcycle suspension system. The damping force varied from 0.941 to 3.858 kN, indicating a growth of around 310%. This study demonstrates that the proposed MRV design and the modification of MRFs could enhance the performance of the motorcycle damping system, as evidenced by the experimental and simulation results. The house of quality (HoQ) demonstrates that the proposed magnetorheological damper (MRD) is significantly superior to its competitors in effectively fulfilling customer requirements and expectations.